Older Workers at L.L.Bean - Estabrook, Wendy (Maine Policy Review, 2015)
Wendy Estabrook reviews L.L.Bean’s policies and practices that support older workers, and employees of all ages, through flexible schedules, generous leave policies, its Employee Assistance Program (EAP), and specific educational offerings for retirement planning.
Keywords: older workers; L.L.Bean; Maine